Normal organizational wrongdoing a critical analysis of theories of misconduct in and by organizations - Palmer, Donald (Oxford : Oxford University Press, 2012)
This work provides an analysis of organisational wrongdoing explaining why individuals and groups behave unethically or illegally, using a range of different theories and case studies.
Includes index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Corporations -- Corrupt practices; Organizational behavior; Commercial crimes; Employee crimes; Business ethics; Social responsibility of business